Customers' perceived website service quality and its effects on e-loyalty among faculty of management studies and commerce undergraduates of university of jaffna - Karunakaran, M. (University of Jaffna, 2022)
Purpose: The purpose of this study is to examine Customers' perceived website service quality of online shopping websites and its effects on e-loyalty. Methodology: This research tested a conceptual framework. Questionnaire data were based on a sample of 300 undergraduates from Faculty of Management Studies and Commerce, University of Jaffna. The suggested research model was tested by using the quantitative way of analysis to find out the influence of website service quality on customer e-loyalty. Findings: This empirical study indicated that, Website service quality contributes significantly to Customer e-loyalty (F= 93.286; P < 0.05) and predicts 54.4 percent of the variation found. Further, website functionality and overall website service quality contribute significantly to customer e-loyalty. The results shows that website functionality and overall service quality positively and statistically effect on customer e loyalty. But customer experience and reputation have not any significant effect on customer e-loyalty. Research Limitations: This study was confined to undergraduates in Faculty of Management studies and Commerce. This study limited to Sri Lankan online shopping websites. The current study uses only few aspects of determinants of website service quality. Implications: The website service quality measurement model elaborated and verified under domestic circumstances for the website service producers can be instrumental in the realisation of this aims both in theory and in practice.
Keywords: Website service quality; Customer e-loyalty; Online shopping